Elimination of manganese toxicity by organic matter, in a Gray Hydromorphic soil - Döbereiner, Johanna; Alvahydo, Roberto (Pesquisa Agropecuaria Brasileira, 2024)
Three greenhouse experiments with beams (Phaseolus vulgaris) were carried out in a grey hydromorphic soil with manganese toxicity to explain previous observations on soybean improvement by the incorporation of weeds. The experiments included the following treatments: Increasing amounts of organic matter (rice straw mixed with fresh grass), clay and sucrose, manganese oxidizing bacteria, lime pelleting of the seeds and liming the soil. All treatments with organic matter reduced the absorption of manganese by the plants and improved considerably their growth, nodulation and nitrogen fixation. Clay had a similar effect although less pronounced and manganese oxidizing organisms showed significant effects on dry weights of plants only. As expected, lime pelleting of the seeds and liming the soil also reduced manganese toxicity. The addition of sucrose increased manganese absorption, reducing drastically the bean growth. It was concluded that the favorable effect of organic matter in manganese toxicity soil was due to the retention of manganese probably in the exchangable form or complexed.